Prevalence of Bullying in Kashmir and Its Relationship with Socio-Economic Status: Understanding Bullying and Socio-Economic Factors in War-Torn Kashmir (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bullying in every school is one of the biggest challenges and it is the common issue found in ever country around the world. From the ages this issue was present in schools around the world and in Indian context its age-old concept too with different names. In every socio-economic section in the societies, it is widely prevalent and is having adverse effects on schoolchildren. The aim of this study is to understand the prevalence of bullying in war torn Kashmir Northern state of India. In addition, the research will try to understand the gender difference in bullying and the relationship of bullying with socio-economic status of their families. The study used Quantitative method for data collection. The study was conducted among students of higher secondary schools in Kashmir valley. The research was conducted among 1003 adolescents (Boys n=501, Girls n=502). The survey scale of English Translated version of Peer Bullying Survey Questionnaire was used to assess the bullying. The results show that the prevalence rates of peer victimization among male and female secondary school students were 25.8 are Victims, 14.0 are Bully, 15.7 are Bully-Victim and 44.6 are neutral and it was found that there is no significant difference among different socio-economic groups and bullying. In short, conclusion the data shows that Kashmir is not different in matter of bullying issues.